Smac mimetic and oleanolic acid synergize to induce cell death in human hepatocellular carcinoma cells. Issue 1 (28th August 2015) - Liese, Juliane; Abhari, Behnaz Ahangarian; Fulda, Simone
Highlights Synthetic lethal interaction of Smac mimetic and oleanolic acid in hepatocellular carcinoma. Cell death caused by combination treatment is ROS-dependent. Smac mimetic and oleanolic acid cooperate to suppress tumor growth in vivo.